Pengaruh Pengembangan Inovasi Produk Ecoxyn Terhadap Efisiensi Kinerja Produksi Dan Kepuasan Konsumen Terhadap Kualitas Produk UMKM Ecoxyn Indonesia: (Studi Kasus Tender Merchandise Gantungan Kunci Wisuda Telkom University) - Arisandi, Daffa Vicky; Umbara, Taufan (eProceedings of Management, 2024)
Through a number of tenders, Ecoxyn succeeded in reaching a major agreement with Telkom University to produce 4500pcs of key chain merchandise in the graduation tender. The significant increase in production capacity prompted thecompany to conduct more in-depth research to meet the tender requirements. However, at the Telkom University graduationtender in November with a quantity of 4500 pcs, several problems arose such as the high risk of rejected goods, highproduction costs and long production times. In response to these challenges, Ecoxyn has made changes in terms of productdesign and technology with the aim of making application easier.Keywords-innovation, product design, efficiency, quality.